AB1008 Ultrasound Assessment of Synovitis in the Wrists and Finger Joints in Healthy Subjects in the Russian Federation: A Comparative Study with Rheumatoid Arthritis. (10th June 2014) - Osipyants, R.; Karateev, D.; Panasyuk, E.; Smirnov, A.; Lukina, G.; Gluchova, S.; Aleksandrova, E.; Volkov, A.; Nasonov, E.
Abstract : Objectives: To evaluate the occurrence of synovitis in healthy subjects detectable by ultrasound (US) and to compare the results of US findings with rheumatoid arthritis (RA). Methods: Thirty-six healthy individuals [30 F/6 M; median age 36.5 (30.5-49) years] and forty-six patients with RA [38 F/8 M; age 48 (39-55) years, p=0.01 vs. healthy subjects; disease duration 58 (36-96) months] were enrolled in the present study. The volunteers were included if no synovitis was suspected clinically and the values for laboratory data (ESR, CRP) were within the normal range. US was performed by a single operator, unaware of clinical data ("Voluson-i" GE, USA) with array transducer (4-13MHz). The US assessment included bilateral of the wrists and the metacarpophalangeal joints (MCP) 1-5 in both groups. MCP joints were evaluated from the dorsal and volar aspects. Grey-scale (GS) US synovial hypertrophy was assessed by quantitative measurement and semiquantitative scale (0-3 grades). Power Doppler (PD) signal was calculated on a semiquantitative scale (0-3). Comparison of US scores was performed applying receiver operating characteristic (ROC) analysis in the patient and control groups. ROC analysis was used for the identification of optimal cut-offs (mm) between "healthy" and "pathologic". Score 0 is considered as "healthy", while scores of 1, 2, and 3 are considered as "pathologic". Results: A total of 984 joints were evaluated: 552 from patients with RA and 432 from healthy controls. In the RA group, US abnormalities were recorded in the wrist – 87% (80/92), in MCP joints - 56% (259/460) compared to 30% (22/72) and 25% (94/360) in the healthy subjects, respectively (p<0, 0001 in all cases). Taking into account only moderate/severe alterations (2 or 3), synovitis (synovial effusion or hypertrophy) was detected more often in patients with RA, than healthy group [76 vs. 11% for the wrist; p<0, 01; 74 vs. 19% for MCP joints; p=0, 01]. There was a statistical difference between groups for the detection of PD of the wrist [46% (42/92) of RA vs. 6.9% (5/72) of the healthy group; p<0, 0001] and MCP joints [50% vs. none; p<0, 0001, respectively]. Furthermore, patients with RA showed a higher-grade PD signal compared to healthy controls who had all joints were scored as PD=1. We found no correlation between US abnormalities in the healthy subjects and demographic characteristics (age or gender). The optimal cut-off point between "healthy" and "pathologic" for GS of MCP joint was found to be 1.95 mm for the dorsal aspect (sensitivity 60.9%, specificity 72.2%) and 0.55 mm - for the volar aspect (sensitivity 69.6%, specificity 83.3%). The area under the ROC curves for GS from the dorsal and volar views were 0.76 (95% CI =0.66 to 0.86, p<0.001) and 0.79 (95% CI =0.69 to 0.89, p<0.001). Conclusions: These results confirmed that synovitis may be found in healthy subjects by US. Low-grade PD and GS scores may not necessarily related to inflammatory arthritis, but high-grade PD is associated with clinical disease activity in patients with RA. US demonstrated to be able to distinguish normal from pathological joints. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5413